Effects of human disturbance and riparian conditions on Odonata (Insecta) assemblages in eastern Amazon basin streams - Oliveira-Júnior, José Max Barbosa de; Marco Júnior, Paulo de; Dias-Silva, Karina; Leitão, Rafael Pereira; Leal, Cecília Gontijo; dos Santos Pompeu, Paulo; Gardner, Toby Alan; Hughes, Robert Mason; Juen, Leandro (Limnologica, 2017)
Riparian vegetation is an important determinant of the physical, chemical, and biological condition of streams, and odonates are useful indicators of riparian condition. To identify environmental factors that structure Odonata assemblages in tropical forest streams, we collected adult odonate specimens and habitat data from 50 stream sites located in the Brazilian municipality of Paragominas (Pará state). We collected 1769 specimens representing 11 families, 41 genera, and 97 species. Of these species, 56 were Zygoptera, and 41 were Anisoptera. Improved environmental condition was reflected in increased Zygoptera species richness and reduced Anisoptera species richness. Channel shading was strongly and positively related to Zygoptera richness, and negatively to Anisoptera richness. Zygoptera species richness, but not Anisoptera species richness, was related positively to bank angle, quantity of wood in the stream bed, electrical conductivity, and decreased water temperature. Altered riparian vegetation structure was the principal determinant of odonate assemblage structure. Our results indicate that maintaining intact riparian vegetation is fundamental for conserving or re-establishing aquatic odonate assemblage structure. © 2017 Elsevier GmbH
Keywords: Anisoptera (dragonflies); Insecta; Odonata; Zygoptera